HISTOPATHOLOGICAL CHANGES IN PLACENTAL TISSUE OF COVID–19 PREGNANT WOMEN DELIVERED AT PAK EMIRATE MILITARY HOSPITAL, RAWALPINDI - Waqar, Samina; Saadia, Aiza; Abbas, Zainab; Akhtar, Farhan; Choudry, Abeera; Baig, Jehan Ara Rafiq (Pakistan Armed Forces Medical Journal, 2020)
Objective: To document the histological changes in the placentas of COVID-19 pregnant women. Study Design: Case series. Place and Duration of Study: Gynaecology department of Pak Emirate Military Hospital, from Mar 2020 to Jul 2020. Methodology: Nine placentas of COVID-19 positive women were included in the study. Placentas of patients with other co-morbid conditions (diabetes, hypertension, pre eclampsia, eclampsia or any infection) were excluded from the study. Results: The most common lesions were avascular, hyalinised, infarcted villi, perivillous and intervillous fibrin deposition, thrombosis of umbilical cord artery and congestion. Thrombosis of chorionic vessels were seen in 5 cases (Mean 0.55, 55.55%). Intervillous thrombosis was seen in 5 cases (Mean 0.55, 55.55%) and chorangiosis was seen in three cases (Mean 0.33, 33.3%). One case of acute chorioamniotis and intervillositis (Mean 0.11, 11.11%) with neutrophilic infiltrate was present, which was confirmed by applying immunohistochemistry with Myeloperoxidase (MPO) stain. Conclusion: In this study, histological changes are seen in nine placentas of COVID-19 affected women, which showed evidence of thrombosis and associated changes. Although new-borns did not show any abnormality, significant histological changes observed, warrant the risk to fetuses like still birth and miscarriages. Further studies with large sample size could possibly make these consequences more clear. Also introduction of treatment like anti thrombotic therapy may be considered to overcome placental changes to avoid their harmful effects.